The genetics of the dog [ - Ruvinsky, Anatoly (CABI, 2012)
This second edition book presents a comprehensive description of all modern topics related to dog genetics from various scientists in the USA, Europe, Australia and Russia. The systematics, phylogeny, domestication and single gene traits are discussed i chapters 1-5, chapters 6-10 are on immunogenetics and genetic diseases, while chapters 11 and 12 presents gene mapping and genome structure of the dog. The genetic aspects of behaviour, reproduction and development are highlighted in chapters 13 to 15, followed by morphological traits and olfactory genetics in chapters 16 and 17, and chapters 18 to 20 discusses genotype testing, pedigree analysis, quantitative genetics and complex traits. Chapters 21 to 23 emphasizes the application of dog genetics in medical research, genetic aspects of performance in working dogs and genomic nomenclature. The book is intended towards researchers, lecturers, students, dog breeders, veterinarians and kennel clubs